(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A geological reconnaissance carried out during Summer 1982 along the lower and middle Shimshal Valley allows to identify some lithostratigraphic units madc up of slates (shaly and sandy deep— sea turbidites), shelf limestones and dolomites. The Upper Paleozoic age of some fossiliferous limestones is well documented. Ultrabasic dykes discordant to both bedding and cleavage intruded slates and dolomites.